Investigating the role of family, personality traits and self-efficacy in shaping students’ entrepreneurial Intentions - Hussain, Tahir; Channa, Nisar Ahmed; Samo, Altaf Hussain (Piccola Impresa / Small Business, 2021)
Recently scholars around the globe have noted the importance of entrepreneurship in creating job opportunities and socio-economic development in both developed and developing economies. Despite this importance, there is lack of research in developing countries regarding antecedents of individuals’ entrepreneurial intentions. Using theoretical framework of social cognitive theory, this research aims to study the effects of family background, personality traits, and self-efficacy on entrepreneurial intentions. To this end, a sample comprised of n = 374 final year university students was utilized to test the hypothesized relationships by employing partial least square structural equation modeling (PLS-SEM) technique. The findings suggest a significant positive impact of family background, personality traits, and self-efficacy on entrepreneurial intentions. In conclusion, the implications of research findings are discussed in detail.